2006
DOI: 10.1152/japplphysiol.01439.2005
|View full text |Cite
|
Sign up to set email alerts
|

Snoring-related energy transmission to the carotid artery in rabbits

Abstract: Epidemiological studies link habitual snoring and stroke, but mechanisms involved are poorly understood. One previously advanced hypothesis is that transmitted snoring vibration energy may promote carotid atheromatous plaque formation or rupture. To test whether vibration energy is present in carotid artery walls during snoring we developed an animal model in which we examined induced snoring (IS)-associated tissue energy levels. In six male, supine, anesthetized, spontaneously breathing New Zealand White rabb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 44 publications
(42 reference statements)
3
58
0
1
Order By: Relevance
“…Snoring may also contribute to cardiovascular risk. 16,17 Effective positional therapy to reduce AHI but with only a small reduction in snoring may be of greatest benefit to patients who regularly sleep alone (5/15 patients in this study and 17% to 25% in others 39,40 ). However, for the majority of positional OSA patients, adjunct or alternative therapies are likely necessary to relieve snoring if snoring is a primary complaint or significant clinical concern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Snoring may also contribute to cardiovascular risk. 16,17 Effective positional therapy to reduce AHI but with only a small reduction in snoring may be of greatest benefit to patients who regularly sleep alone (5/15 patients in this study and 17% to 25% in others 39,40 ). However, for the majority of positional OSA patients, adjunct or alternative therapies are likely necessary to relieve snoring if snoring is a primary complaint or significant clinical concern.…”
Section: Discussionmentioning
confidence: 86%
“…13,14 Snoring is a cardinal feature of OSA and results from vibrations of a partially obstructed upper airway during sleep. 15 Snoring may have deleterious health consequences in its own right, including vibration damage-induced carotid atherosclerosis 16,17 and potentially carotid plaque rupture and stroke. Snoring very frequently disrupts the sleep of others, particularly affecting bed partner sleep and quality of life.…”
Section: Subjectsmentioning
confidence: 99%
“…11 Recent evidence in rabbits suggests that snoring promotes energy transmission to the carotid artery that could also be involved in atherosclerosis progression. 33 In addition, the association between OSA and atherosclerosis could be mediated by the presence of HTN, a condition that is also associated with proatherogenic factors, such as endothelial dysfunction and inflammation. 34 Typical patients with OSA share several risk factors for cardiovascular disease, including obesity and HTN, well established causes of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the efficiency of the baroreflex may be disrupted by continuously heightened sympathetic output in snorers (66). Although it is possible that intermittent hypoxia, repetitive desaturations and resultant increased sympathetic activity may contribute to cardiovascular complications, it has been suggested that snoring vibrations themselves have the potential to damage carotid arterial walls and contribute to plaque rupture as observed in atherosclerosis (67). A further possibility is that the association between snoring and cardiovascular events is mediated by obesity.…”
Section: Cardiovascular Andmentioning
confidence: 99%